2016
DOI: 10.1016/j.gheart.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Prevalence, Awareness, Treatment, and Control in Selected LMIC Communities: Results From the NHLBI/UHG Network of Centers of Excellence for Chronic Diseases

Abstract: Background Hypertension is the leading cause of cardiovascular disease and premature death worldwide. The prevalence of this public health problem is increasing in low-and-middle income countries (LMICs) both in urban and rural communities. Objective To examine hypertension prevalence, awareness, treatment, and control in adults 35-74 years old from urban and rural communities in LMICs in Africa, Asia and South America. Methods We analyzed data from 7 population-based cross-sectional studies in selected co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
62
2
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 37 publications
11
62
2
11
Order By: Relevance
“…Complex interactions between metabolic and neurohormonal pathways, with resultant alterations in insulin resistance, the renin-angiotensin-aldosterone system, and sympathetic tone, could explain the occurrence of HTN amongst people who are overweight/obese. [44][45][46][47][48][49] The awareness and treatment rates of 63.4% and 96.7% in our study are similar to the 62.4% and 93.3% rates in Pakistan, and the 69% and 90.8% rates in Peru, reported in a review of HTN in a slightly younger population in 9 LMIC by Irazola et al 31 Our awareness rates were higher than the 44.6% 22 lower than rates reported in high-income countries. 30,32 Our control rates were significantly lower than the 46% and 71% obtained in Pakistan and Peru, respectively, in a review of HTN in a slightly younger population in 9 LMIC by Irazola et al 31 Our rates were considerably higher than those found in an elderly population in other LMICs.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Complex interactions between metabolic and neurohormonal pathways, with resultant alterations in insulin resistance, the renin-angiotensin-aldosterone system, and sympathetic tone, could explain the occurrence of HTN amongst people who are overweight/obese. [44][45][46][47][48][49] The awareness and treatment rates of 63.4% and 96.7% in our study are similar to the 62.4% and 93.3% rates in Pakistan, and the 69% and 90.8% rates in Peru, reported in a review of HTN in a slightly younger population in 9 LMIC by Irazola et al 31 Our awareness rates were higher than the 44.6% 22 lower than rates reported in high-income countries. 30,32 Our control rates were significantly lower than the 46% and 71% obtained in Pakistan and Peru, respectively, in a review of HTN in a slightly younger population in 9 LMIC by Irazola et al 31 Our rates were considerably higher than those found in an elderly population in other LMICs.…”
Section: Resultssupporting
confidence: 86%
“…29,30 These differences could be due to heterogeneity in sampling methods and cut-off age for the elderly population, ranging from 35 to 74 years across various studies. 1,15,26,27,[30][31][32][33] Compared with younger adults, older individuals are at least twice more likely to develop HTN. 33 This is in coherence with global trends, and recent estimates project a further increase in these values.…”
Section: Resultsmentioning
confidence: 99%
“…38,39 Since high BP is primarily asymptomatic, structured community programs play an important role in the diagnosis and have proven effective in diagnosis patients unaware they have hypertension. 40,41 3 | CURRENT EVIDENCE AND GUIDELINES Treatment of ISH in older adults was somewhat unclear until randomized studies such as the Systolic Hypertension in the Elderly Program (SHEP), 8 the Systolic Hypertension in Europe trial (Syst-Eur), 42 and the Hypertension in the Very Elderly Trial (HYVET) 43 showed significant CV benefits on lowering SBP in patients with ISH. All these four trials defined ISH as SBP ≥160 and DBP <90 mmHg.…”
Section: Diagnosis Of Hypertensionmentioning
confidence: 99%
“…Una de las mayores limitaciones de la aplicabilidad del SPRINT en Latinoamérica es el uso de equipos para la medición de la PA , dado que en los países latinoamericanos aún es frecuente el uso del esfigmomanómetro de mercurio o aéreo 24 . En el SPRINT, se realizaron 3 mediciones a los pacientes sentados, después de cinco minutos de reposo antes de la medición, sin conversaciones durante el periodo de reposo o medición; condiciones difícilmente alcanzables por el personal de salud en Latinoamérica.…”
Section: Aplicabilidad Del Sprint En Latinoamérica: Guías De Prácticaunclassified